Assessment of combining ability in purple corn parents under line × tester mating design using GGE biplot - Nurul Mufidah; Arifin Noor Sugiharto; Budi Waluyo (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Mufidah N, Sugiharto AN, Waluyo B. 2021. Assessment of combining ability in purple corn parents under line × tester mating design using GGE biplot. Biodiversitas 22: 4545-4554. One strategy to increase corn quality is the development of new corn cultivars by incorporating the character of nutritional content. The study aims to obtain information on the combining ability of purple corn lines as well as determine the best parental lines for purple corn hybrid development using the GGE biplot approach. This study used 24 hybrids generated from crossings of 8 purple corn lines with 3 testers, which were crossed using a line × tester mating design. Plant performance was assessed using a randomized block design of three replications. The F-test was used to assess and test the experiment variance. The combining ability of purple corn lines was examined using the GGE biplot method. The result showed that the GGE biplot approach successfully identified the best combiner and combinations generated between purple corn lines and non-purple corn lines. Purple corn lines P1Y1 had the best general combining ability for fresh ear yield and total anthocyanin content, meanwhile, P1Y2 had the best general combining ability in most of the agronomic traits, namely ear diameter, shelled ear weight, number of grains row-1, and as well as total anthocyanin content. These 2 lines were also identified as the best parent chosen in the best combination in this study.